Comparative Analysis of Barriers and Challenges in Adoption of Electronic Health Record System in Government and Private Hospitals of Islamabad - Ghazala Jawwad; Maleha Asim; Amanat Ali; Humaira Fayyaz Khan; Aiman Farogh Anjum; Abdul Qudoos Arain (Journal of Rawalpindi Medical College)
Objective: The purpose of this study was to identify the barriers and challenges in adoption of the EHR system in hospitals of Islamabad and to compare the barriers and challenges faced in adopting and running of electronic health record system in government and private hospitals of Islamabad.